Improving children’s cooperativeness during magnetic resonance imaging using interactive educational animated videos: a prospective, randomised, non-inferiority trial - Evelyn Gabriela Utama; Seyed Ehsan Saffari; Phua Hwee Tang (Singapore Medical Journal)
Introduction: A previous prospective, randomised controlled trial showed that animated videos shown to children before magnetic resonance imaging (MRI) scan reduced the proportion of children needing repeated MRI sequences and improved confidence of the children staying still for at least 30 min. Children preferred the interactive video. We hypothesised that the interactive video is non-inferior to showing two videos (regular and interactive) in improving children’s cooperativeness during MRI scans. Methods: In this Institutional Review Board-approved prospective, randomised, non-inferiority trial, 558 children aged 3–20 years scheduled for elective MRI scan from June 2017 to March 2019 were randomised into the interactive video only group and combined (regular and interactive) videos group. Children were shown the videos before their scan. Repeated MRI sequences, general anaesthesia (GA) requirement and improvement in confidence of staying still for at least 30 min were assessed. Results: In the interactive video group (n = 277), 86 (31.0%) children needed repeated MRI sequences, two (0.7%) needed GA and the proportion of children who had confidence in staying still for more than 30 min increased by 22.1% after the video. In the combined videos group (n = 281), 102 (36.3%) children needed repeated MRI sequences, six (2.1%) needed GA and the proportion of children who had confidence in staying still for more than 30 min increased by 23.2% after the videos; the results were not significantly different between the two groups. Conclusion: The interactive video group demonstrated non-inferiority to the combined videos group.